Exploratory Study of Fecal Cortisol, Weight, and Behavior as Measures of Stress and Welfare in Shelter Cats During Assimilation Into Families of Children With Autism Spectrum Disorder - Carlisle, Gretchen K.; Johnson, Rebecca A.; Koch, Colleen S.; Lyons, Leslie A.; Wang, Ze; Bibbo, Jessica; Cheak-Zamora, Nancy (Frontiers in Veterinary Science, 2021)
Background: Cats are a common companion animal (CA) in United States households, and many live in families of children with autism spectrum disorder (ASD). The prevalence of ASD is one in 54 and many children have behavior challenges as well as their diagnostic communication disorders. Objective: Benefits of CAs for children with ASD have been identified, but little is known about the welfare of CAs in these homes. This study explored the welfare of cats (N = 10) screened for ideal social and calm temperament using the Feline Temperament Profile (FTP) and adopted by families of children with ASD. Methods: Cat stress was measured using fecal cortisol, weight and a behavior stress measure (Cat Stress Score). Measures were taken at baseline in the shelter, two to three days after adoption, and at weeks six, 12 and 18. Result: Outcome measures suggested the adopted cats’ stress levels did not increase post-adoption; however, the small sample size limited analytical power and generalizability. Conclusion: This study provides preliminary evidence for the success of cat adoption by families of children with ASD, when cats have been temperament screened and cat behavior educational information is provided. Further research is warranted to confirm these findings.